ANALISIS PEMBELAJARAN KEYBOARD DASAR DI KURSUS MUSIK MUSICAISHA - Nur, Salma Agnia Fauziah (Jurnal Seni dan Pembelajaran, 2023)
This study aims to analyze keyboard learning at the Musicaisha Music Course in Tasikmalaya City. The subjects of this study were teachers/coaches and students in the Musicaisha Music Course. This study focused on learning components such as materials, methods, strategies, keyboard learning used in the Musicaisha  Music Course in Tasikmalaya City. This study uses a qualitative descriptive research method. Data obtained through direct observation during learning. Interviews were conducted with teachers/keyboard trainers as well as documentation in the form of photos of the learning process. The findings of this study indicate that the keyboard learning process at the Musicaisha Music Course is going well. This is supported by a private learning process. The stages of delivering the material were in accordance with the knowledge and abilities of the students, the first meeting students were given basic material regarding introduction to the keyboard until the sixth meeting, students were able to play the keyboard musical instrument by playing the simple song Ode To Joy even though it was not perfect.